Differential uranyl(v) oxo-group bonding between the uranium and metal cations from groups 1, 2, 4, and 12; a high energy resolution X-ray absorption, computational, and synthetic study. Issue 42 (6th September 2019) - Zegke, Markus; Zhang, Xiaobin; Pidchenko, Ivan; Hlina, Johann A.; Lord, Rianne M.; Purkis, Jamie; Nichol, Gary S.; Magnani, Nicola; Schreckenbach, Georg; Vitova, Tonya; Love, Jason B.; Arnold, Polly L.
Abstract : Uranyl Pacman takes them all: the bonding of s- and d-block cations to uranyl is compared by experiment, spectroscopy and theory. Abstract : The uranyl(vi ) 'Pacman' complex [(UO2 )(py)(H2 L)] A (L = polypyrrolic Schiff-base macrocycle) is reduced by Cp2 Ti(η 2 -Me3 SiCCSiMe3 ) and [Cp2 TiCl]2 to oxo-titanated uranyl(v ) complexes [(py)(Cp2 Ti III OUO)(py)(H2 L)] 1 and [(ClCp2 Ti IV OUO)(py)(H2 L)] 2 . Combination of Zr II and Zr IV synthons with A yields the first Zr IV –uranyl(v ) complex, [(ClCp2 ZrOUO)(py)(H2 L)] 3 . Similarly, combinations of Ae 0 and Ae II synthons (Ae = alkaline earth) afford the mono-oxo metalated uranyl(v ) complexes [(py)2 (ClMgOUO)(py)(H2 L)] 4, [(py)2 (thf)2 (ICaOUO)(py) (H2 L)] 5 ; the zinc complexes [(py)2 (XZnOUO)(py)(H2 L)] (X = Cl 6, I 7 ) are formed in a similar manner. In contrast, the direct reactions of Rb or Cs metal with A generate the first mono-rubidiated and mono-caesiated uranyl(v ) complexes; monomeric [(py)3 (RbOUO)(py)(H2 L)] 8 and hexameric [(MOUO)(py)(H2 L)]6 (M = Rb 8b or Cs 9 ). In these uranyl(v ) complexes, the pyrrole N–H atoms show strengthened hydrogen-bonding interactions with the endo -oxos, classified computationally as moderate-strength hydrogen bonds. Computational DFT MO (density functional theory molecular orbital) and EDA (energy decomposition analysis), uranium M4 edge HR-XANES (High Energy Resolution X-ray Absorption Near Edge Structure) and 3d4f RIXS (Resonant Inelastic X-ray Scattering) have been used (the latter two for the first time for uranyl(v ) in 7 (ZnI)) to compare the covalent character in the U V –O and O–M bonds and show the 5f orbitals in uranyl(vi ) complex A are unexpectedly more delocalised than in the uranyl(v ) 7 (ZnI) complex. The Oexo –Zn bonds have a larger covalent contribution compared to the Mg–Oexo /Ca–Oexo bonds, and more covalency is found in the U–Oexo bond in 7 (ZnI), in agreement with the calculations.